Message Processing The Science of Creating Understanding - Gasiorek, Jessica; Open Textbook Library (Open Textbook Library, 2018)
The text provides an upper-level undergraduate introduction and explanation of the social and cognitive processes involved in human communication, focusing on how people create understanding.
Chapter 1: Introduction to Message Processing -- Chapter 2: Foundational Concepts -- Chapter 3: Media -- Chapter 4: Communicative Codes -- Chapter 5: Traditional Models of Human Communication -- Chapter 6: The Inferential Model of Human Communication
In English.
Description based on print resource
Keywords: Communication -- Textbooks